2020
DOI: 10.1111/dth.13229
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in resistant livedoid vasculopathy: Analysis of a case series

Abstract: We report a retrospective analysis the efficacy of high‐dose intravenous immunoglobulins on 9 patients with Livedoid vasculopathy for whom resistant to immunosuppressants plus anticoagulants or could not be prescribed. Intravenous immunoglobulins were used 2 g/kg per month in these patients. The treatment induced stabilization of the disease and all patients demonstrated improvement with IVIg. Complete and partial clinical response was achieved in 6 and 3 patients respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 10 publications
(12 reference statements)
0
24
0
3
Order By: Relevance
“… 10 Further retrospective case series such as Bounfour et al including 5 patients and Ozden et al including 9 patients with IVIG 2 g/kg bodyweight over a period of 3 days also reported good therapeutic response regarding pain and ulceration. 13 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Further retrospective case series such as Bounfour et al including 5 patients and Ozden et al including 9 patients with IVIG 2 g/kg bodyweight over a period of 3 days also reported good therapeutic response regarding pain and ulceration. 13 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9] In addition, a response to IVIG was shown in smaller collectives. 10,12,18 LV is often associated with extreme pain and severe restrictions in patients' private and professional lives. This study shows a significant improvement in the symptoms of LV in terms of pain, ulceration and restrictions in everyday life under therapy with IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of intravenous immunoglobulins (IVIG) for LV have been reported. [4][5][6][7][8] However, no standard protocol of the regimen with IVIG for LV has been established, and its superiority over other medications especially in severe cases intractable to conventional medications has not been confirmed. Here, we report a case of severe LV refractory to intense immunosuppressive and anti-thrombotic agents, in which only two cycles of IVIG resulted in remission for 7 years.…”
Section: Long-term Remission Of Severe Livedoid Vasculopathy Treated With a Short Course Of Intravenous Immunoglobulinmentioning
confidence: 99%
“…In previous reports, IVIG was administered at a dose of 1-2 g/kg and repeated for several to more than 10 cycles regularly at 4-week intervals. [5][6][7][8] Most patients achieved dramatic improvement or remission in skin manifestations after the first to the third cycle.…”
Section: Long-term Remission Of Severe Livedoid Vasculopathy Treated With a Short Course Of Intravenous Immunoglobulinmentioning
confidence: 99%
“…Then, the viruses spread through the bloodstream and mainly in the lungs, gastrointestinal tract, and heart, presumably concentrated in the tissues expressing ACE2, the receptor of SARS‐CoV‐2. This phase occurs around 7‐14 after the onset of the symptoms when the virus starts a second attack, which is also the main cause of the aggravation of symptoms 93 . At this time, pulmonary lesions became worse, and chest CT scans show imaging changes consistent with COVID‐19 94 .…”
Section: Skin Conditions Related To Hypercoagulability That Show Histmentioning
confidence: 99%